2020
DOI: 10.1080/26895293.2020.1790431
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG14 promotes non-small cell lung cancer progression by sponging miR-382-5p

Abstract: Long non-coding RNAs (lncRNAs) are involved in development of non-small cell lung cancer (NSCLC) by interacting with microRNAs (miRNAs) and/or mRNAs. However, the function of most lncRNAs in NSCLC remains unclear. Reverse transcription-quantitative PCR (RT-qPCR) and western blot were applied for detection of mRNA/miRNA and protein level. Interaction between LncRNA small nucleolar RNA host gene 14 (SNHG14) and miR-382-5p was validated by dual luciferase reporter assay. Cell proliferation and apoptosis was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…One hundred thirteen studies required further screening based on their title and abstract. Subsequently, 47 studies were eligible to read the full text, and eventually, 21 cohort studies ( Zhang Y. Y. et al, 2019 ; Zhang Z. et al, 2019 ; Deng et al, 2019 ; Ji et al, 2019 ; Li et al, 2019 ; Pei et al, 2019 ; Zhao et al, 2019 ; Zhao and Huang, 2019 ; Zhang H. et al, 2020 ; Zhang K. et al, 2020 ; Chen et al, 2020 ; Zhang W. et al, 2020 ; Luo et al, 2020 ; Sun et al, 2020 ; Wang and Wen, 2020 ; Xu et al, 2020 ; Zhou et al, 2020 ; Wang et al, 2021a ; Wang et al, 2021b ; Feng et al, 2021 ; Liao et al, 2021 ) were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred thirteen studies required further screening based on their title and abstract. Subsequently, 47 studies were eligible to read the full text, and eventually, 21 cohort studies ( Zhang Y. Y. et al, 2019 ; Zhang Z. et al, 2019 ; Deng et al, 2019 ; Ji et al, 2019 ; Li et al, 2019 ; Pei et al, 2019 ; Zhao et al, 2019 ; Zhao and Huang, 2019 ; Zhang H. et al, 2020 ; Zhang K. et al, 2020 ; Chen et al, 2020 ; Zhang W. et al, 2020 ; Luo et al, 2020 ; Sun et al, 2020 ; Wang and Wen, 2020 ; Xu et al, 2020 ; Zhou et al, 2020 ; Wang et al, 2021a ; Wang et al, 2021b ; Feng et al, 2021 ; Liao et al, 2021 ) were included in the meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of SNHG14 was detected using qPCR within the included studies. In addition, 16 studies Zhang Z. et al, 2019;Ji et al, 2019;Li et al, 2019;Pei et al, 2019;Zhao and Huang, 2019;Zhang H. et al, 2020;Zhang K. et al, 2020;Chen et al, 2020;Zhang W. et al, 2020;Luo et al, 2020;Sun et al, 2020;Wang and Wen, 2020;Feng et al, 2021;Liao et al, 2021) reported on OS, and 17 Zhang Z. et al, 2019; Frontiers in Genetics frontiersin.org Frontiers in Genetics frontiersin.org Deng et al, 2019;Ji et al, 2019;Zhang H. et al, 2020;Zhang K. et al, 2020;Chen et al, 2020;Zhang W. et al, 2020;Luo et al, 2020;Sun et al, 2020;Wang and Wen, 2020;Xu et al, 2020;Zhou et al, 2020;Wang et al, 2021a;Wang et al, 2021b;Feng et al, 2021;Liao et al, 2021) on clinical outcomes. The NOS scores of included studies were as follows: two studies (Zhang Z. et al, 2019;Zhang W. et al, 2020) with a NOS score of 8, five studies (Ji et al, 2019;Zhang K. et al, 2020;Wang et al, 2021a;Wang et al, 2021b;Feng et al, 2021) with a NOS score of 7, eight studies Deng et al, 2019;Pei et al, 2019;Chen et al, 2020;…”
Section: Studies Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplication, we further screened 113 studies based on their title, abstract. 51 studies need to read the full text, and eventually 21 [19,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] were included in this meta-analysis (Figure 1). This study included 1,080 patients, all from China.…”
Section: Studies Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The expression of SNHG14 was detected by qPCR in 21 studies. Among the included studies, 16 [19, 27, 28, 31-33, 35-39, 41-45]reported on OS and 17 [19,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]43] on clinical outcomes. The NOS scores for all included studies were ≥7, which indicates that the methodological quality of included studies was high.…”
Section: Studies Characteristics and Quality Assessmentmentioning
confidence: 99%